Problem jedności nauki w świetle sporu o realizm - Sikora, Marek (Filozofia Nauki, 2015)
Etymologically, unity comes from Latin unum, meaning one. In the context of science, unity is regarded as included in the metaphysical, epistemological, and semantic notion that the universe is one and explainable by means of scientific methods which lead to revealing the truth. Such a concept of unity is supported by thinkers who either adopt realism on metaphysical, epistemological, and semantic grounds or limit it to the epistemological (and sometimes also semantic) level. Such limitations make the philosophical dispute over the unity of science too shallow, especially in the context of the debate between realist and anti-realist positions. The key point in the problem of the unity of science is to differentiate between three levels of the discussion about realism and antirealism. My argument is that on one the hand we can accept metaphysical realism in some sense, while on the other it is still possible to question the unity of science.